Visual communication : more than meets the eye - Jamieson, G. H. (G. Harry) (University of Chicago Press ; Intellect Books, 2007)
We exist in a visual culture. The importance of reading and interpreting signs has become a rapidly increasing concern in recent years. This book offers an intricate theoretical perspective regarding the study of visual communication and expands the academic arena for debate concerning the visual.